MAiD and the Death of Dignity - Pullman, Daryl (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The concept of human dignity figures prominently in discussions about medical assistance in dying. Yet the notion of ‘dignity’ is often ambiguous. This paper seeks to clear up some of this ambiguity by distinguishing two different but related conceptions of dignity, the one a fundamentally moral notion (‘Dignity’—upper case) and the other a more aesthetic conception (‘dignity’—lower case). The dynamic relationship that exists between the moral notion of ‘Dignity’ and its aesthetic counterpart (‘dignity’) is examined. While a pluralistic society requires both notions, only the objective moral notion (Dignity) is adequate to serve as the foundation of a fundamental legal regime. While any pluralistic society must provide opportunities for the expression of subjective aesthetic notions of dignity, the latter can neither serve as the foundation of a comprehensive public ethic in general, nor can it set the parameters of a public policy on medicalized homicide. Indeed, the unmitigated expansion of a particular notion of ‘dignity’ threatens to expunge the more fundamental conception of Dignity that serves as the foundation of any liberal democratic society.